Mediation Role of Job Satisfaction on the Influence of Emotional Intelligence and Transformational Leadership on Organizational Commitment - Jufrizen, Jufrizen; Nadia, Nadia; Muslih, Muslih (Publisher Cv. Inara, 2022)
The purpose of this study was to determine and analyze the effect of emotional intelligence on organizational commitment, the influence of transformational leadership on organizational commitment, the effect of emotional intelligence on job satisfaction, the effect of transformational leadership on job satisfaction, the effect of job satisfaction on organizational commitment, the influence of emotional intelligence on organizational commitment through job satisfaction, and the effect of transformational leadership on organizational commitment through job satisfaction. In this study, using associative research with a sample of 81 respondents who are employees of the North Sumatra Provincial Health Office. Data collection techniques using interviews and a list of statements such as questionnaires and data analysis techniques using partial least squares (smartpls) to test the seven hypotheses proposed in this study. The results of the research show that emotional intelligence has no effect on organizational commitment, transformational leadership has no effect on organizational commitment, emotional intelligence has a significant effect on job satisfaction, transformational leadership has a significant effect on job satisfaction, job satisfaction has no significant effect on organizational commitment, emotional intelligence has a significant effect on commitment. organization through job satisfaction (in other words job satisfaction acts as a mediator).